Pengabdian Masyarakat Sebagai Proses Pembentukan Kematangan Profesional Berbasir Pilar Ulul Albab - Hardanti, Kandita Deswira (Maliki Interdisciplinary Journal, 2026)
Community service through Student Field Work (KKM) is an integral part of the implementation of the Tri Dharma of higher education, which aims to bridge academic knowledge with the real needs of the community. In practice, KKM at the village level is often understood as a short-term administrative activity oriented towards fulfilling institutional obligations, so that it has not yet fully produced a sustainable social impact. This condition shows a gap between the normative objectives of KKM and the reality of complex social problems in rural communities, such as stunting, poor parenting, extreme poverty, low technological literacy, and challenges in strengthening religious moderation. This study aims to analyze how the integration of the Ulul Albab pillar and the Sustainable Development Goals (SDGs) framework can be used as a basis for implementing KKM in Kaliasri Village to encourage sustainable social change. The Ulul Albab paradigm, which emphasizes a balance between the spiritual (dzikir), intellectual (fikir), and social praxis (amal shalih) dimensions, is considered relevant to strengthening students' values, ethics, and social responsibility in community service. This study uses a qualitative approach with the Participatory Action Research (PAR) method, which places students and village communities as active subjects in the process of problem identification, program planning, activity implementation, and evaluation. This study uses a qualitative approach with the Participatory Action Research (PAR) method, which places students and village communities as active subjects in the process of problem identification, program planning, activity implementation, and reflective and continuous evaluation. The results of the study show that integrating the values of remembrance, reflection, and righteous deeds within the framework of the SDGs can strengthen the critical awareness of students and the community, increase the active participation of villagers, and encourage a sense of ownership of the KKM program. A participatory approach accompanied by long-term assistance has proven to be more effective in building the capacity of village human resources than interventions that are temporary and ceremonial in nature. Thus, Ulul Albab-based community service not only contributes to solving village social problems, but also plays a strategic role in shaping the professional maturity of students as ethical, reflective, and sustainability-oriented agents of social change.